Pengaruh Sistem Informasi Akuntansi, Pengendalian Internal, dan Budaya Organisasi Terhadap Kinerja Perusahaan BUMD Kabupaten Gresik - Faradisa Mezza; Umaimah Umaimah (Akuntansi, 2024)
BUMDs utilize provincial guidelines or perda, to do their capabilities. It is common knowledge that BUMD Gresik's performance is anticipated to decline in 2023. The board should unquestionably choose and recognize issues, then, at that point, execute the vital answers for further develop execution. Bookkeeping data frameworks are without a doubt important to support business execution. Furthermore, there is a connection between's hierarchical culture and inward control with organization achievement. The reason for this study is to decide how the impact of hierarchical culture, inside control, and bookkeeping data frameworks on business tasks at BUMD Gresik Rule. This study utilized quantitative procedure and gathered information utilizing a poll overview. Several types of tests were calculated using the SPSS software to examine the collected data. The outcomes showed that hierarchical culture has an importance worth of 0.002, while bookkeeping data frameworks and inside control have an importance worth of 0.000 with an alpha degree of 0.05. These discoveries show that authoritative culture, inner control, and bookkeeping data frameworks all affect business accomplishment at BUMD Gresik Regime (Ha acknowledged, Ho dismissed).